Casting light on multiple sclerosis heterogeneity: the role of HLA-DRB1 on spinal cord pathology. - DeLuca, G; Alterman, R; Martin, J; Mittal, A; Blundell, S; Bird, S; Beale, H; Hong, L; Esiri, M (2013)
Clinical heterogeneity in multiple sclerosis is the rule. Evidence suggests that HLA-DRB1*15 may play a role in clinical outcome. Spinal cord pathology is common and contributes significantly to disability in the disease. The influence of HLA-DRB1*15 on multiple sclerosis spinal cord pathology is unknown. A post-mortem cohort of pathologically confirmed cases with multiple sclerosis (n = 108, 34 males) with fresh frozen material available for genetic analyses and fixed material for pathology was used. HLA-DRB1 alleles were genotyped to select a subset of age- and sex-matched HLA-DRB1*15-positive (n = 21) and negative (n = 26) cases for detailed pathological analyses. For each case, transverse sections from three spinal cord levels (cervical, thoracic and lumbar) were stained for myelin, axons and inflammation. The influence of HLA-DRB1*15 on pathological outcome measures was evaluated. Carriage of HLA-DRB1*15 significantly increased the extent of demyelination (global measure 15+: 23.7% versus 15-: 12.16%, P = 0.004), parenchymal (cervical, P < 0.01; thoracic, P < 0.05; lumbar, P < 0.01) and lesional inflammation (border, P = 0.001; periplaque white matter, P < 0.05) in the multiple sclerosis spinal cord. HLA-DRB1*15 influenced demyelination through controlling the extent of parenchymal inflammation. Meningeal inflammation correlated significantly with small fibre axonal loss in the lumbar spinal cord (r = -0.832, P = 0.003) only in HLA-DRB1*15-positive cases. HLA-DRB1*15 significantly influences pathology in the multiple sclerosis spinal cord. This study casts light on the role of HLA-DRB1*15 in disease outcome and highlights the powerful approach of using microscopic pathology to clarify the way in which genes and clinical phenotypes of neurological diseases are linked.